Association of Concurrent Healthy Eating and Regular Physical Activity with Cardiovascular Disease Risk Factors in U.S. Youth. Issue 1 (September 2015) - Loprinzi, Paul D.; Lee, I-Min; Andersen, Ross E.; Crespo, Carlos J.; Smit, Ellen
Purpose: Examine whether concurrently consuming a healthy diet and regularly being physically active among U.S. youth is more favorably associated with cardiovascular disease (CVD) biomarkers than other physical activity and dietary patterns. Design: Cross-sectional. Setting: United States (National Health and Nutrition Examination Survey) 2003–2006. Subjects: Two thousand six hundred twenty-nine youth (6–17 years). Measures: Healthy Eating Index (HEI), accelerometer-determined physical activity, biomarkers, and anthropometry. Four categories were created: consuming a healthy diet (top 40% of HEI) and active (sufficient to meet guidelines); unhealthy diet and active; healthy diet and inactive; and unhealthy diet and inactive. Analysis: Multivariable regression. Results: Children consuming a healthy diet and who were active had significantly lower waist circumference (β = −5.5, p < .006), C-reactive protein (CRP) (β = –.2, p < .006), and triglycerides (β = −27.9, p < .006) than children consuming an unhealthy diet and who were inactive. Children engaging in both healthy behaviors had significantly lower CRP (β = –.11, p < .001) and total cholesterol levels (β = −7.8, p = .004) than those only engaging in sufficient activity; there were no significant differences in biomarker levels among children engaging in both healthy behaviors and those only consuming a healthy diet. No associations were significant for adolescents. Conclusion: Concurrent healthy eating and regular physical activity among children is favorably associated with CVD biomarkers when compared with unhealthy diet and inactivity.